Palinología del tránsito Cenomaniense/Turoniense en la sección de Puentedey (Burgos, España) - Barrón, Eduardo; Comas-rengifo, María José; Peyrot, Daniel; Barroso-barcenilla, Fernando; Feist-burkhardt, Susanne (Coloquios de Paleontología, 2009)
The studied section is located near the village of Puentedey in the Province of Burgos, Spain. The area corresponds to the NW part of the North-Castilian Platform. Twenty-two samples were collected from middle Cenomanian-middle Turonian carbonate rocks. The palynological study allowed the identification of twenty-eight marine and forty-two terrestrial palynomorphs taxa. Marine palynomorphs are dominant in the assemblages from the late Cenomanian and the Cenomanian-Turonian boundary but are less abundant in the early Turonian. The terrestrial component is dominated by pollen grains attributed to the Normapolles Group. The presence of Atlantopollis microreticulatus, A. reticulatus, Limaipollenites? vilaflorensis, Complexiopollis cf. normis and Tricolpites cf. amplifissus indicates a late Cenomanian - early Turonian age which is in agreement with data provided by ammonoid fauna. Two palaeovegetation types have been identified. The first is a coastal vegetation characterized by gymnosperms (mainly Araucariaceae and Cheirolepidiaceae); the second vegetation type correspond to an open forest community dominated by anemophilous angiosperms - Normapolles producers- with an understorey composed of vascular cryptogams.
Keywords: Systematic; Palaeobiogeography; Palaeoecology; Normapolles; Cenomanian/Turonian boundary; North Castilian Platform